Interview with Professor Edwin van Teijlingen - Subedi, Madhusudan; Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2023)
Edwin van Teijlingen is Dutch by birth and a Professor of Reproductive Health at Bournemouth University in the south of England. He has achieved a PhD in Medical Sociology at the University of Aberdeen, UK. Prof. Edwin van Teijlingen connected with Nepal while supervising Nepali PhD scholars in UK, and he has been a frequent visitor to Nepal since 2006. He has supervised more than 35 PhDs, among which 13 are Nepali. He has examined more than 50 PhDs. He has published around 300 academic papers and book chapters in health promotion, midwifery, and health services research. He serves as a peer reviewer for worldwide famous health journals such as PLOS One and BMC Pregnancy and Childbirth. He delivered a speech to the Members of Parliamentarians in Kathmandu in 2016 as part of a workshop to promote evidence-based policymaking. He is a committee member on various grant-awarding bodies in the UK, Belgium, the Netherlands, Norway, Switzerland, and the USA. He is a visiting Professor at the Centre for Disability Studies, Mahatma Gandhi University, Kerala in India (2020-present); the School of Health Sciences at the University of Nottingham in England (2017-2026); Nobel College, affiliated with Pokhara University, Nepal (2012-present); and Manmohan Memorial Institute of Health Sciences affiliated with Tribhuvan University (2009-present). We would like to express our gratitude for his acceptance to share personal and academic lives, which can inspire young and energetic scholars in Nepal and elsewhere.